Golf style homes and collections inspired by the course and clubhouse - Moon, Vicky (Clarkson Potter/Publishers, 2010)
Golf Style is a joyous celebration of the history, traditions, personalities, innovations, challenges, and verdant beauty associated with the game, as well as a limitless source of inspiration for anyone, duffer or pro, who wants to make the sport a part of his or her life both on and off the green.